RATIONALE RATIO DEFENCE ASSETS IN RECEIVABLES AND PAYABLES OF THE COMPANY - Lysa, O. V. (Science and Transport Progress, 2007)
The article is devoted to peculiarities of managing the turnover assets within accounts receivable and payable of an enterprise, and substantiation of approaches to defining their optimum correlation.